The Parliamentary Rules of Procedure of the Sixth Grand National Assembly - Mihaylova, Ekaterina (Yearbook of the Law Department, 2021)
Under consideration in the article are the debates and the adopted provisions in the Rules of Procedure of the VIth Grand National Assembly. A special emphasis is placed on the typical and characteristic features of the Rules of Procedure as well as on the particularities that it reveals, as being adopted for a parliament that is bound to adopt entirely new Constitution. There are some provisions in the Rules of Procedure that are relevant both to the constituent power and to the constituted power. Under analysis are the adopted provisions that are contrary to the provisions in force at the time of the 1879 Tarnovo Constitution, as well as the rule of law principles.